Transformasi Digital Raisa Bakery: Penerapan AI, Website, Sosial Media dan E-Commerce dalam Meningkatkan Perekonomian UMKM Desa Kuta Tualah - Rudi Gunawan; Gema Suaria; Zaimah Panjaitan; Siti Julianita Siregar; Devia Nasution (Jurnal Masyarakat Indonesia (Jumas), 2025)
This community service program intends to develop and implement digital transformation in Raisa Bakery UMKM in Kuta Tualah Village, focusing on the application of AI, website development, social media, and e-commerce to enhance the local economy. To expand market reach and improve operational efficiency, the program includes the creation of a digital identity through logo and packaging design using AI technology, building a business website on the WordPress platform, and using social media sites like FB, IG, and TikTok to interact with consumers and raise brand exposure. Furthermore, the Shopee e-commerce platform was used to introduce bakery products to a wider market. The results of this digital transformation implementation show a significant increase in sales, product visibility, and customer interaction. The adoption of digital technology has reduced the limitations of traditional marketing methods and opened new opportunities for Raisa Bakery to compete in a larger market. This program provides evidence that digital transformation can be an effective strategy for empowering UMKM in rural areas and boosting the local economy. This success can serve as a model for other UMKMs seeking to adopt digital technology for business development.